Ionic polymer based on flexible main chain, anion exchange membrane and preparation method thereof

By using flexible backbone-based ion polymers in the anion exchange membrane, combining acetal and ketal reactions, the problem of insufficient performance of anion exchange membrane in the prior art is solved, and a high-performance anion exchange membrane is realized, which is suitable for a variety of energy conversion devices.

CN119875052AActive Publication Date: 2025-04-25WUHAN POLYTECHNIC UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510361695.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-04-25
Estimated Expiration
2045-03-26

AI Technical Summary

Technical Problem

It is difficult to develop high-performance anion exchange membranes in the prior art, especially while maintaining high ion conductivity, mechanical properties and alkali resistance stability, it is difficult to achieve high solubility and good mechanical properties.

Method used

An anion exchange membrane with high ionic conductivity, chemical stability and mechanical properties are formed by reacting acetal and/or ketal through a full carbon flexible polymer backbone, aldehyde or ketone and 1,7-dichloro-4-heptanone quaternization product.

Benefits of technology

Anion exchange membrane with high stability, high ion conductivity and high mechanical properties is achieved. It is suitable for fuel cells and water electrolysis and other devices, improving the overall efficiency and durability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875052A_ABST
    Figure CN119875052A_ABST
Patent Text Reader

Abstract

The invention provides an ionic polymer based on a flexible main chain, an anion exchange membrane and a preparation method thereof. The preparation method of the anion exchange membrane comprises the following steps: mixing 1, 7-dichloro-4-heptanone and a trimethylamine solution in a first organic solvent to obtain N1, N1, N1, N7, N7, N7-hexamethyl-4-oxoheptane-1, 7-ammonium dichloride; mixing the ionic polymer with a hydroxyl-containing all-carbon flexible polymer main chain and aromatic aldehyde and / or aromatic ketone in the presence of a second organic solvent and a catalyst to obtain an ionic polymer based on the flexible main chain; and mixing the ionic polymer based on the flexible main chain with a third organic solvent, drying the mixed solution to form a membrane, and soaking the membrane in an alkali solution to obtain the anion exchange membrane of which the anion is hydroxyl. The ionic polymer and / or anion exchange membrane based on the flexible main chain prepared by the invention has the characteristics of excellent mechanical properties, high ionic conductivity, low swelling ratio, high antioxidant stability, high alkali-resistant stability, high fuel cell performance and high water electrolysis performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells and water electrolysis, and in particular to an ionic polymer based on a flexible main chain, an anion exchange membrane and a preparation method thereof. Background Art

[0002] Anion exchange membrane (AEM) is a type of polymer electrolyte composed of cations fixed on the main chain and freely moving anions. It can be used in energy conversion devices such as zero-gap alkaline water electrolyzers and anion exchange membrane fuel cells. With the country's increasing attention to hydrogen production and use in recent years, the demand for the research and development of high-performance AEM has become more and more significant. AEM plays the role of conducting ions and isolating electrodes in the device, so it needs to have high ion conductivity and excellent mechanical properties. And because the working environment is often alkaline, AEM also needs to have high alkali resistance and stability. In addition, since it is used as a catalyst layer ionomer, the ionic polymer used to prepare AEM also needs to have good solubility.

[0003] Acetals are organic compounds with two alkoxy groups and one hydrogen on the same carbon. Ketals are organic compounds with two alkoxy groups and two hydrocarbon groups on the same carbon. Acetals and ketals are unstable in acidic aqueous solutions, but stable to bases and oxidants. This structure is widely used to protect carbonyl groups. This type of structure has a natural stability advantage in the preparation of AEMs. The literature (Int J Hydrogen Energ. 46, 2021, 37007-37016) used the acetal reaction of 4-imidazolylbenzaldehyde and hydroxyl groups to synthesize imidazole-functionalized polyvinyl alcohol as a cross-linker for functional macromolecules, and then the macromolecular cross-linker reacted with brominated polyphenylene ether to synthesize cross-linked AEMs. The study found that after immersion in 1 M NaOH solution for 1000 h, the mechanical properties and ionic conductivity of the c-91 membrane with the best comprehensive performance showed a more obvious attenuation, but the authors used spectroscopic characterization to confirm that the degradation occurred in the imidazole ring, not the acetal group. The authors used a cross-linking strategy to combine flexible chains with rigid chains. Although it helps to obtain a rigid and flexible anion exchange membrane, the ion exchange capacity and ion conductivity of the target product are both low due to the low ion density. For example, the ion exchange capacity of c-91 is 1.54 mmol / g, and the ion conductivity at 80°C is 78.8 mS / cm. The literature (Macromolecules 54, 2021, 7900-7909) uses acetal reaction to graft trifluoromethylbenzaldehyde and 4-imidazolecarboxaldehyde on polyvinyl alcohol, and uses the Menxiu gold reaction of methylene bromide and imidazole to introduce a long-chain cross-linker containing cations into the anion exchange membrane. After the alkaline stability experiment (6M NaOH, 80°C, 240h), the loss of ion conductivity is close to 35%. The authors used nuclear magnetic resonance carbon spectroscopy experiments to confirm that the cause of AEM degradation is that the carbon atom adjacent to the cation is nucleophilized by the hydroxyl group, resulting in the opening of the carbon chain of the cross-linker, and the degradation site is not the acetal group. Due to the high crosslinking density, the obtained AEMs have high ion exchange capacity (1.8~2.9 mmol / g), high water content (282%~726%, room temperature), and thus high ionic conductivity (29.6~66.1, room temperature). However, the high water content leads to a higher swelling rate and thus poor mechanical properties (0.7~1.4 MPa). In addition, this type of crosslinked AEMs cannot obtain soluble ionic polymers and cannot be used as ionomers in the catalyst layer of membrane electrodes.

[0004] In summary, although acetals and ketals have high alkali resistance, it is still necessary to develop high-performance ion polymers and anion exchange membranes based on this type of structure. Summary of the invention

[0005] In view of this, the present invention proposes an ionic polymer based on a flexible main chain, an anion exchange membrane and a preparation method thereof having high stability, high ionic conductivity and high mechanical properties.

[0006] In a first aspect, the present invention provides an ionic polymer based on a flexible main chain, wherein the polymer is as shown in formula (I): (I); In formula (I), x, y, z, and t all represent the molar proportion of each structural unit in the ionic polymer; wherein the value range of 2x+2y is 0.4~1.0, and 2x+2y+z+t=1.0; and R includes at least one benzene ring.

[0007] On the basis of the above technical solution, preferably, the value range of x is 0.1~0.5, the value range of y is 0.1~0.5, the value range of z is 0~0.6, and the value range of t is 0~0.4.

[0008] In a second aspect, the present invention relates to a method for preparing the above-mentioned flexible main chain-based ionic polymer, wherein the flexible main chain-based ionic polymer is prepared by acetalization and / or ketalization of a full-carbon flexible polymer main chain, an aldehyde or ketone and a quaternization product of 1,7-dichloro-4-heptanone.

[0009] First, the main chain of the all-carbon flexible polymer of the present invention contains hydroxyl groups (-OH), which, as active functional groups, can ensure good compatibility between the polymer and other reactants, provide reaction sites for subsequent chemical modifications, and enable the hydroxyl-containing polymer to effectively combine with other reactants, thereby introducing new functional side chains. The presence of hydroxyl groups helps promote intermolecular hydrogen bonding or other types of crosslinking, which can improve the mechanical properties and thermal stability of the material. In addition, the acetal and / or ketal structure formed by the acetal and / or ketal reaction can further stabilize the polymer network and give the material better physical properties.

[0010] Secondly, the quaternization product of 1,7-dichloro-4-heptanone has excellent ionic conductivity, which can significantly enhance the application potential of the final polymer as an ionic conductor and electrolyte material, and is suitable for energy storage devices such as batteries and supercapacitors. The compound exhibits high chemical and thermal stability, ensuring the long-term performance of the material under harsh conditions, which is essential for the development of high-performance, long-life products. In addition, the functional side chains introduced by specific quaternization agents not only enhance the ionic conductivity, but also provide additional functionalization sites for subsequent chemical modification, such as two chlorine atoms, which increases the design flexibility of the material. At the same time, 1,7-dichloro-4-heptanone is easy to undergo quaternization reaction, and the reaction is highly selective and controllable, allowing precise control of product properties and achieving high customization of the final material properties. The quaternization product has good compatibility with the hydroxyl-containing all-carbon flexible polymer backbone and other reactants (such as aromatic aldehydes or ketones), promoting the formation of a multifunctional composite structure, while also maintaining environmental adaptability and being able to perform stably under various conditions.

[0011] By adopting the above technical solution, not only functional ionic groups and aromatic structures are successfully introduced while maintaining the original flexibility of the polymer, the ionic conductivity, chemical stability and thermal stability of the material are significantly improved, but also the mechanical properties and processability are enhanced.

[0012] On the basis of the above technical solution, preferably, the all-carbon flexible polymer main chain is a hydroxyl-containing all-carbon flexible polymer main chain, and its structure is shown in formula (a): (a); In formula (a), m and n both represent the molar proportion of each structural unit in the polymer; wherein m+n=1.0.

[0013] On the basis of the above technical solution, the aldehyde or ketone is an aromatic aldehyde or aromatic ketone; preferably, the aromatic aldehyde and / or the aromatic ketone is selected from at least one of the following structures: .

[0014] On the basis of the above technical solution, the 1,7-dichloro-4-heptanone is as shown in the following formula (b): (b).

[0015] On the basis of the above technical solution, preferably, the quaternization product of 1,7-dichloro-4-heptanone is as shown in the following formula (c): (c).

[0016] On the basis of the above technical solution, preferably, the method comprises the following steps: S1, 1,7-dichloro-4-heptanone and trimethylamine solution undergo a Menxiu gold reaction in a first organic solvent to obtain N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-diammonium chloride; S2. The hydroxyl-containing all-carbon flexible polymer main chain undergoes acetal and / or ketal reaction with the N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-diammonium chloride and aromatic aldehydes and / or aromatic ketones prepared in step S1 under the action of a second organic solvent and a catalyst to obtain an ionic polymer based on a flexible main chain.

[0017] By adopting the above technical means, the present invention introduces specific functional side chains (such as ionic groups and aromatic aldehyde / ketone structures), which can significantly improve the chemical diversity and functionality of all-carbon flexible polymers. These modifications can enhance the conductivity, thermal stability, mechanical flexibility and other physical and chemical properties of the material, making the material more suitable for application in fields with high performance requirements.

[0018] On the basis of the above technical solution, preferably, in step S1, the amount of trimethylamine added is 3 to 5 times the molar amount of chlorine atoms in the 1,7-dichloro-4-heptanone; the mass volume ratio of the 1,7-dichloro-4-heptanone and the first organic solvent is 1 g: (5 to 10 mL).

[0019] By adopting the above technical scheme, the appropriate ratio ensures efficient quaternization reaction, so that 1,7-dichloro-4-heptanone is fully converted into N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-diammonium chloride, thereby maximizing ionic conductivity and chemical stability. At the same time, controlling the amount of solvent between 5~10 mL / g not only ensures good dispersion and contact of the reactants, but also avoids the low reaction efficiency caused by excessive solvent or the increase of side reactions caused by too little solvent. In order to ensure the efficiency of the Menxiujin reaction, an excess of trimethylamine is required, and the optimal amount is 3~5 times the excess. Too much will cause waste of trimethylamine, and too little will easily lead to incomplete quaternization reaction and reduce the ionic conductivity of subsequent ion polymers and anion exchange membranes. Similarly, too high a solvent ratio will dilute the reaction system, reduce the reaction rate and yield; too low a ratio may lead to poor dissolution of the reactants, cause excessive local concentration, produce uncontrollable side reactions, and affect the quality and consistency of the final material.

[0020] On the basis of the above technical solution, preferably, in step S1, the first organic solvent is at least one of methanol, ethanol and tetrahydrofuran.

[0021] Based on the above technical solution, preferably, in step S1, the temperature of the Menxiu gold reaction is 30-50° C., and the reaction time is 24-36 h.

[0022] On the basis of the above technical solution, in the step S1, the temperature of the Menxiu gold reaction is independently selected from any value of 30°C, 40°C, 50°C or a range between any two of the above.

[0023] On the basis of the above technical solution, in the step S1, the Menxiu gold reaction is independently selected from any value of 24 h, 28 h, 32 h, 36 h or a range between any two of the above.

[0024] On the basis of the above technical scheme, preferably, in step S1, after the reaction is completed, the product of the Menxiu gold reaction is freed from the solvent by a rotary evaporator to obtain the product N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-diammonium chloride.

[0025] On the basis of the above technical scheme, preferably, in step S2, the molar ratio of the N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-diammonium chloride to the hydroxyl-containing all-carbon flexible polymer main chain is (0.2~0.9):1; the molar ratio of the aromatic aldehyde and / or aromatic ketone to the hydroxyl-containing all-carbon flexible polymer main chain is (0.2~0.8):1; the mass volume ratio of the hydroxyl-containing all-carbon flexible polymer main chain to the second organic solvent is 1g:(20~40 mL).

[0026] By adopting the above technical scheme, efficient acetal and / or ketal reactions are ensured, so that functional side chains can be introduced uniformly and appropriately into the polymer main chain, thereby achieving a high degree of customization of material properties. The appropriate molar ratio ensures the optimal balance between ionic conductivity and mechanical flexibility, while avoiding excessive functionalization that causes increased material rigidity or decreased solubility. In addition, the appropriate amount of aromatic aldehydes and / or aromatic ketones can enhance the conjugated system and electronic effects of the material, improving the optical and electrical properties without causing unnecessary side reactions or structural instability.

[0027] Based on the above technical solution, preferably, in step S2, the second organic solvent is dimethyl sulfoxide (DMSO).

[0028] On the basis of the above technical solution, preferably, in step S2, the first catalyst comprises at least one of hydrochloric acid, concentrated sulfuric acid, trifluoroacetic acid, p-trifluoromethylbenzenesulfonic acid or trifluoromethanesulfonic acid. In the present invention, the first catalyst is added to adjust the pH value of the reaction solution to 3-4.

[0029] Based on the above technical solution, preferably, in step S2, the temperature of the acetal and / or ketal reaction is 60-80° C., and the polymerization reaction time is 6-24 h.

[0030] On the basis of the above technical solution, in step S2, the temperature of the acetal and / or ketal reaction is independently selected from any value of 60°C, 70°C, 80°C or a range between any two of the above.

[0031] On the basis of the above technical scheme, in the step S2, the acetal and / or ketal reaction is independently selected from any value of 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h or a range between any two of the above.

[0032] On the basis of the above technical solution, preferably, in step S2, an alkaline solution is used as a reaction terminator after the reaction is completed.

[0033] More preferably, the reaction terminator is selected from 0.5 mol / L sodium carbonate solution or 1 mol / L sodium hydroxide solution.

[0034] By adopting the above technical scheme, using 0.5 mol / L sodium carbonate solution or 1 mol / L sodium hydroxide solution as a reaction terminator not only helps to improve the quality, stability and purity of the final product, but also simplifies the subsequent processing steps and reduces the operational difficulty and safety risks.

[0035] In a third aspect, the present invention relates to the application of the above-mentioned ionic polymer based on a flexible main chain in anion exchange membranes and catalyst layer ionomers.

[0036] By adopting the above technical solutions, the ionomer can provide higher ion exchange capacity, better dimensional stability and lower water swelling rate, effectively improving the selectivity and conductivity of the anion exchange membrane, reducing membrane resistance and improving the overall efficiency of the system. At the same time, in the ionomer of the catalytic layer, it promotes the uniform distribution and contact between catalyst particles, enhances the accessibility of electrode active sites, and further improves the rate and selectivity of the catalytic reaction. In addition, the multifunctional properties of the material also allow customized design according to specific application scenarios, broadening its application range in fuel cells, electrolyzers and other energy-related technologies.

[0037] In a fourth aspect, the present invention provides a method for preparing an anion exchange membrane. The method, based on the preparation of an ionic polymer based on a flexible main chain, further includes: S3, mixing the ionic polymer based on the flexible main chain of step S2 with a third organic solvent, drying the mixed solution to form a membrane, and mixing the membrane with an alkaline solution to obtain an anion exchange membrane whose anion is hydroxide.

[0038] On the basis of the above technical solution, preferably, in step S3, the mass volume ratio of the flexible main chain-based ionic polymer to the third organic solvent is 1 g: (20-50 mL).

[0039] Based on the above technical solution, preferably, the third organic solvent is dimethyl sulfoxide.

[0040] On the basis of the above technical solution, preferably, in step S3, the mixing temperature is 40-60° C., and the mixing time is 2-4 h, wherein the purpose of mixing is dissolution.

[0041] On the basis of the above technical solution, the mixing temperature is independently selected from any value of 40° C., 50° C., 60° C. or a range between any two of the above values.

[0042] On the basis of the above technical solution, preferably, the mixing time is independently selected from any value among 2 h, 3 h, 4 h or a range value between any two of the above.

[0043] On the basis of the above technical solution, preferably, in step S3, the drying temperature is 70-90°C.

[0044] On the basis of the above technical solution, the drying temperature is independently selected from any value among 70°C, 75°C, 80°C, 85°C, 90°C or a range between any two of the above.

[0045] On the basis of the above technical solution, preferably, the alkali solution includes NaOH and / or KOH solution, and the concentration of the alkali solution is 0.5~2.0 mol / L.

[0046] Based on the above technical solution, preferably, the temperature of the alkaline solution is 30-80°C.

[0047] On the basis of the above technical solution, the temperature of the alkaline solution is independently selected from any value of 30°C, 40°C, 50°C, 60°C, 70°C, 80°C or a range between any two of the above.

[0048] Based on the above technical solution, preferably, the soaking time is 12 to 24 hours.

[0049] On the basis of the above technical solution, the soaking time is independently selected from any value among 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h or a range value between any two of the above.

[0050] On the basis of the above technical solution, preferably, during the soaking, the fresh alkaline solution is replaced 3 to 5 times.

[0051] In a fifth aspect, the present invention relates to an anion exchange membrane prepared by the above preparation method.

[0052] In a sixth aspect, the present invention relates to the application of anion exchange membranes in fuel cells and water electrolysis.

[0053] The ionic polymer based on a flexible main chain and its preparation method and application, an anion exchange membrane and its preparation method provided by the present invention have the following beneficial effects compared with the prior art: (1) The ion polymer / anion exchange membrane prepared by the present invention has the characteristics of high ion exchange capacity and high ion conductivity, because two cationic side chains are grafted simultaneously at each functional site. At the same time, due to the hydrophobicity and rigidity of the side chains containing benzene rings, the anion exchange membrane of the present invention has the characteristics of high wet membrane strength on the one hand, and on the other hand, it helps to induce microscopic phase separation in the anion exchange membrane to promote ion conduction efficiency. In addition, due to the high alkali resistance of the acetal and / or ketal structure, the high alkali resistance of the hydroxyl-containing all-carbon flexible polymer main chain and the high alkali resistance of the fatty quaternary ammonium root cation, the ion polymer / anion exchange membrane of the present invention has the characteristics of high chemical stability. Compared with the benzene ring chain, the anion exchange membrane based on the flexible main chain prepared by the present invention has high oxidation resistance.

[0054] (2) The preparation method of the ionic polymer and anion exchange membrane disclosed in the present invention has simple steps and is easy to implement in large-scale production by casting method.

[0055] (3) The ionic polymer electrolyte of the present invention has good solubility, and its polymer solution can be used as an ionomer to prepare a catalyst ink together with a catalyst and a dispersant for preparing an anion membrane or a gas diffusion electrode coated with a catalyst layer, thereby improving the stability and durability of the device operation.

[0056] (4) The ionomer provided by the present invention is composed of highly stable chemical structural units, and therefore has high alkali stability and high oxidation resistance when used for the catalyst layer ionomer and the preparation of anion exchange membrane.

[0057] (5) The ion polymer / anion exchange membrane disclosed in the present invention has the characteristic of high ion conductivity due to its hydrophilic and hydrophobic phase separation characteristics.

[0058] (6) The anion exchange membrane provided by the present invention regulates the water absorption and swelling rate of the anion exchange membrane by adding hydrophobic side chains containing benzene rings, thereby improving the mechanical strength of the wet film of the polymer and enhancing the rigidity of the membrane.

[0059] (7) The method for preparing the ion polymer / anion exchange membrane provided by the present invention can achieve the characteristics of adjustable physical and chemical properties by adjusting the grafting degree of cations and benzene-containing side chains, as well as the structure of the benzene-containing side chains.

[0060] (8) The anion exchange membrane of the present invention can be used as a diaphragm electrolyte in devices such as fuel cells and water electrolysis due to its high ionic conductivity, mechanical properties and chemical stability.

[0061] (9) The anion exchange membrane of the present invention has a low glass transition temperature due to the main chain of a hydroxyl-containing all-carbon flexible polymer main chain. By introducing a benzene ring-containing side chain, the glass transition temperature can be regulated, so that the anion exchange membrane meets the requirements of the hot pressing process conditions, further improving the operating performance of the anion exchange membrane in the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0063] Figure 1 The nuclear magnetic resonance hydrogen spectrum of the structure of N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-diammonium chloride of the present invention ( 1 HNMR) spectra; Figure 2 is a hydrogen nuclear magnetic resonance spectrum of the anion exchange membrane in Example 1 of the present invention; Figure 3 This is the H2-O2 single cell performance curve of the anion exchange membrane at 80°C in Example 1 of the present invention; Figure 4 The mechanical properties curves of the anion exchange membrane in Example 2 of the present invention in dry and wet states respectively; Figure 5 is a curve diagram showing the change of ion conductivity of anion exchange membrane with temperature in Example 2 of the present invention; Figure 6 This is a small angle X-ray scattering (SAXS) image of the anion exchange membrane in Example 3 of the present invention.

[0064] Figure 7 The anion exchange membrane in Example 3 of the present invention is 1M, 80 o C histogram of ionic conductivity before and after 1440 h of immersion; Figure 8 is a curve diagram showing the change of water content of anion exchange membrane with temperature in Example 4 of the present invention; Fig. 9 is a curve diagram showing the change of swelling rate of anion exchange membrane with temperature in Example 4 of the present invention; Fig.10 is a linear sweep voltammetry (LSV) curve of the anion exchange membrane at 60° C. and 80° C. in Example 5 of the present invention; Fig.11 This is a bar graph of the mass retention rate of the anion exchange membrane in Example 6 of the present invention after being immersed in Fenton's reagent for 6 hours. DETAILED DESCRIPTION

[0065] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0066] 1,7-dichloro-4-heptanone, p-fluorobenzaldehyde, 3,4,5-trifluorobenzaldehyde, 4-(trifluoromethyl)benzaldehyde, 2,2,2-trifluoroacetophenone, 4'-(trifluoromethyl)acetophenone, 2,2,2,4'-tetrafluoroacetophenone, hydrochloric acid, concentrated sulfuric acid, trifluoroacetic acid, p-trifluoromethylbenzenesulfonic acid, trifluoromethanesulfonic acid, polyvinyl alcohol PVA-P767001 (Mw = 190000, alcoholysis degree = 98-99 mol%) used in the following examples were purchased from Shanghai Maclean Biochemical Technology Co., Ltd., and the methanol solution of trimethylamine (3.2M) was purchased from Beijing Bailingwei Technology Co., Ltd. Ethylene-vinyl alcohol copolymer was purchased from Kuraray Co., Ltd., with the brand name F171B (vinyl alcohol accounts for 68%). The remaining materials not shown are all commercially available conventional products.

[0067] The test methods for the relevant test items in the following embodiments 1 to 6 are as follows: (1) Ionic conductivity The ionic resistance of the anion exchange membrane was measured by the AC impedance method. The measurement frequency range was 1Hz-4MHz and the potential amplitude was 5 mV. The measured resistance Nyquist curve was fitted. The intersection of the curve and the real axis Z' was the ionic resistance value of the anion exchange membrane. R The formula for calculating conductivity is as follows: ; σ is the ionic conductivity, l is the distance between the two electrodes, R is the ionic resistance of the sample being measured, S is the cross-sectional area of ​​the membrane.

[0068] (2) Ion exchange capacity (IEC) The test method includes: using Mohr titration method to test the ion exchange capacity of AEM, the calculation formula is as follows: ; In the formula, c (AgNO3) is the concentration of AgNO3 solution, v (AgNO3) is the volume of AgNO3 solution consumed, m dry(Cl - ) is the dry weight of the AEM.

[0069] Water content The test method includes: taking the anion as OH - AEM, wipe the water on its surface with filter paper, and weigh its mass in the saturated water state The membrane was then placed in a vacuum drying oven at 65°C and dried for 12 hours until the membrane mass no longer decreased, and then its mass was weighed. , the formula for calculating the moisture content is as follows: .

[0070] (4) Mechanical strength: The mechanical performance test includes the tensile strength and elongation at break of the anion exchange membrane of the sample under test in a fully wet state. The operating rate of the instrument stretching is 5 mm / min.

[0071] (5) Alkali resistance and stability The test conditions are: 80℃, immersion in 1 mol / L KOH solution for 1440 hours. The retention rate of ionic conductivity is used as the measurement standard.

[0072] Planar swelling ratio (SD) The test method includes: first record the dry film plane size , then test the counter ion as OH - The plane dimensions of the AEM after full swelling with water at different temperatures are recorded as , the formula for calculating the plane dimensional stability is as follows: .

[0073] Antioxidant stability The test conditions include: immersing the ion exchange membrane prepared in this example in Fenton's reagent at 40° C. for 168 hours. The ratio of Fenton's reagent is 3 wt % hydrogen peroxide and 4 ppm ferrous ions.

[0074] Fuel cell performance test The fuel cell operating temperature is 80°C, the gas flow rate of H2 and O2 is 500 sccm, and the gas is 100% humidified. The cathode and anode in the membrane electrode are both made of carbon-supported platinum as catalyst, with a catalyst loading of 0.4 mg / cm 2 The ionomer prepared in the example is used as the catalyst layer ionomer. The anion exchange membrane prepared in the example is used as the electrolyte membrane in the fuel cell device.

[0075] Water electrolysis performance in a zero-gap electrolyzer The cathode uses a Pt / C catalyst, the anode uses a NiFe2O4 catalyst, the membrane electrode ionomer uses the ionic polymer prepared in this embodiment, and the anion exchange membrane prepared in the embodiment is used as the electrolyte diaphragm in the water electrolyzer. The electrolyte solution in the electrolytic cell is a 1 M KOH solution. The LSV scanning speed is 10 mV / s, and the scanning range is 1.2-2.0 V.

[0076] Example 1 This embodiment provides an ionic polymer and an anion exchange membrane based on a flexible main chain, which are prepared by the following method: (1) In a 250 mL single-necked round-bottom flask, add 4.9 g of 1,7-dichloro-4-heptanone and 68 mL of trimethylamine methanol solution to 25 mL of methanol, and react under sealed conditions at 40°C with magnetic stirring for 36 h. After the reaction, remove the methanol solvent and excess unreacted trimethylamine on a rotary evaporator until a yellow oily viscous liquid is obtained. This liquid is the product of quaternization of 1,7-dichloro-4-heptanone, N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-dichloroammonium, and its hydrogen nuclear magnetic resonance spectrum is shown in the following figure: Figure 1 shown.

[0077] (2) In a 100 mL two-necked round-bottom flask, 2 g of PVA was dissolved in 40 mL of DMSO at 80°C. After it was completely dissolved and cooled to room temperature, the above-synthesized N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-diammonium chloride, 6.3 g of 4-(trifluoromethyl)benzaldehyde and 1.2 mL of trifluoroacetic acid were added. The temperature was raised to 60°C and the reaction was stirred for 12 h. After the reaction was completed, the reaction solution was added dropwise to a 0.5 M Na2CO3 aqueous solution to obtain an orange crude product. The crude product was crushed with a crusher, and the solution was washed with a large amount of deionized water until it was neutral. Finally, it was placed in a vacuum drying oven at 60°C and dried for 24 h to obtain a quaternized acetal and ketal polymer with a chloride anion and a hydrophobic side chain of 4-(trifluoromethyl)phenyl. Its specific structure is shown below:

[0078] (3) In a 50 mL two-necked round-bottom flask, add 0.4 g of the above-mentioned polymer electrolyte with chloride anion type and 4-(trifluoromethyl)phenyl as the hydrophobic side chain to 15 mL of DMSO solvent, stir at 60°C for 3 h until it is completely dissolved, cast the solution on a 8 cm × 8 cm flat and clean glass plate, and then place it in an 80°C electric oven to obtain a chloride anion exchange membrane with a thickness of about 45 μm through solvent evaporation. Finally, soak the chloride anion exchange membrane in a 60°C, 1 mol / L potassium hydroxide solution for 12 hours, replace the fresh alkali solution 3 times during the period, and finally rinse the residual floating alkali on the membrane surface with deionized water until the pH of the aqueous solution is 7, thus obtaining an anion exchange membrane with hydroxide as the anion. Its nuclear magnetic resonance hydrogen spectrum is shown as follows: Figure 2 As shown, the anion exchange membrane is placed in deionized water with nitrogen and stored. Its specific structure is as follows:

[0079] Among them, x is 0.1, y is 0.2, z is 0.4, and t is 0.

[0080] The IEC of the anion exchange membrane prepared in this example is 1.75 mmol·g -1 ; The ionic conductivity at 80°C is 135.5 mS·cm -1 The water content is 50.2%, the swelling rate is 9.3%; in the dry state, the tensile strength is 75.2 MPa, the elongation at break is 23.5%; the quality retention rate after the antioxidant stability test is 96.6%; the ionic conductivity retention rate after the alkali resistance stability test is 92.1%.

[0081] The test results of the ionomer prepared in this example as the ionomer of the catalyst layer are as follows: Figure 3 As shown. Figure 3 The results show that the discharge curve of the fuel cell assembled with the ion polymer and anion exchange membrane prepared in this embodiment shows that the open circuit voltage of the battery is 1.02 V and the maximum power density is 825.0 mW / cm 2 , which proves that the ionic polymer and anion exchange membrane in Example 1 have good applicability in the field of fuel cells.

[0082] Example 2 This embodiment provides an ionic polymer and an anion exchange membrane based on a flexible main chain, which are prepared by the following method: (1) In a 250 mL single-necked round-bottom flask, add 5.6 g of 1,7-dichloro-4-heptanone and 78 mL of trimethylamine methanol solution to 30 mL of methanol, and react under magnetic stirring at 40°C for 36 h under sealed conditions. After the reaction, remove the methanol solvent and excess unreacted trimethylamine on a rotary evaporator until a yellow oily viscous liquid is obtained, which is the product of quaternization of 1,7-dichloro-4-heptanone, N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-diammonium chloride.

[0083] (2) In a 100 mL two-necked round-bottom flask, 2 g of EVOH was dissolved in 40 mL of DMSO at 80°C. After it was completely dissolved and cooled to room temperature, the above-synthesized N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-diammonium chloride, 5.10 g of p-fluorobenzaldehyde and 1.5 mL of concentrated hydrochloric acid were added. The temperature was raised to 80°C and stirred for 6 h. After the reaction was completed, the reaction solution was added dropwise to a 0.5 M Na2CO3 aqueous solution to obtain an orange crude product. The crude product was crushed with a crusher, and the solution was washed with a large amount of deionized water until it was neutral. Finally, it was placed in a vacuum drying oven at 60°C and dried for 24 h to obtain a quaternized acetal and ketal polymer with a chloride anion and a p-fluorophenyl hydrophobic side chain. Its specific structure is shown below:

[0084] (3) In a 50 mL two-necked round-bottom flask, add 0.4 g of the above-mentioned polymer electrolyte with chloride anion type and p-fluorophenyl as the hydrophobic side chain to 15 mL of DMSO solvent, stir at 60°C for 3 h until it is completely dissolved, cast the solution on a 8 cm × 8 cm flat and clean glass plate, and then place it in an 80°C electric oven to obtain a chloride anion exchange membrane with a thickness of about 45 μm through solvent evaporation. Finally, soak the chloride anion exchange membrane in a 60°C, 1 mol / L potassium hydroxide solution for 12 hours, replace the fresh alkali solution 3 times during the period, and finally rinse the residual floating alkali on the membrane surface with deionized water until the pH of the aqueous solution is 7, that is, the anion exchange membrane with hydroxide anion is obtained, and the anion exchange membrane is stored in deionized water with nitrogen. Its specific structure is shown below:

[0085] Among them, x is 0.1, y is 0.2, z is 0.08, and t is 0.32.

[0086] The ion exchange capacity (IEC) of the anion exchange membrane prepared in this example is 1.72 mmol·g -1The moisture content at 80°C was 37.2%, and the swelling rate was 4.5%. The quality retention rate after the antioxidant stability test was 95.8%. The ionic conductivity retention rate after the alkali resistance stability test was 92.9%.

[0087] The mechanical properties test results of the anion exchange membrane prepared in this example are as follows: Figure 4 As shown. Figure 4 As can be seen from the results, the tensile strength of the anion exchange membrane prepared in this embodiment is higher than 80 MPa under dry conditions, and the elongation at break is greater than 25%. The tensile strength wet film strength under full wet conditions is higher than 35 MPa, and the elongation at break is higher than 300%. This mechanical property can support the anion exchange membrane to be used as a diaphragm material in an electrochemical device.

[0088] The ion conductivity test results of the anion exchange prepared in this example are as follows Figure 5 As shown. Figure 5 The results show that the anion exchange membrane prepared in Example 2 has a o The ionic conductivity at C is 125.6 mS·cm -1 , meeting the conditions for it to efficiently conduct charge as a polymer electrolyte in electrochemical devices.

[0089] Example 3 This embodiment provides an ionic polymer and an anion exchange membrane based on a flexible main chain, which are prepared by the following method: (1) In a 250 mL single-necked round-bottom flask, add 5.6 g of 1,7-dichloro-4-heptanone and 78 mL of trimethylamine methanol solution to 30 mL of methanol, and react under magnetic stirring at 40°C for 36 h under sealed conditions. After the reaction, remove the methanol solvent and excess unreacted trimethylamine on a rotary evaporator until a yellow oily viscous liquid is obtained, which is the product of quaternization of 1,7-dichloro-4-heptanone, N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-diammonium chloride.

[0090] (2) In a 100 mL two-necked round-bottom flask, 2 g of EVOH was dissolved in 40 mL of DMSO at 80 °C. After it was completely dissolved and cooled to room temperature, the above-synthesized N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-dichloroammonium, 3.3 g of 3,4,5-trifluorobenzaldehyde and 1.8 mL of trifluoroacetic acid were added. The temperature was raised to 60 °C and the reaction was stirred for 10 h. After the reaction was completed, the reaction solution was added dropwise to a 0.5 M Na2CO3 aqueous solution to obtain an orange crude product. The crude product was crushed with a crusher, and the solution was washed with a large amount of deionized water until it was neutral. Finally, it was placed in a vacuum drying oven at 60 °C and dried for 24 h to obtain a quaternized acetal and ketal polymer with a chloride anion and a hydrophobic side chain of 3,4,5-trifluorophenyl. Its specific structure is shown below:

[0091] (3) In a 50 mL two-necked round-bottom flask, add 0.4 g of the above-mentioned polymer electrolyte with chloride anion type and 3,4,5-trifluorophenyl hydrophobic side chain to 15 mL of DMSO solvent, stir at 60°C for 4 h until it is completely dissolved, cast the solution on a 8 cm × 8 cm flat and clean glass plate, and then place it in an 80°C electric oven to obtain a chloride anion exchange membrane with a thickness of about 45 μm through solvent evaporation. Finally, soak the chloride anion exchange membrane in a 60°C, 1 mol / L potassium hydroxide solution for 12 hours, replace fresh alkali solution 3 times during the period, and finally rinse the residual floating alkali on the membrane surface with deionized water until the pH of the aqueous solution is 7, that is, the anion exchange membrane with hydroxide anion is obtained, and the anion exchange membrane is stored in deionized water with nitrogen. Its specific structure is shown below:

[0093] Among them, x is 0.1, y is 0.1, z is 0.28, and t is 0.32.

[0094] The IEC of the anion exchange membrane prepared in this example is 1.97 mmol·g -1 ; The ionic conductivity at 80℃ is 131.2mS·cm -1 The water content is 45.2%, the swelling rate is 7.5%; in the dry state, the tensile strength is 68.4 MPa, the elongation at break is 33.8%; the quality retention rate after the antioxidant stability test is 97.6%; the ionic conductivity retention rate after the alkali resistance stability test is 93.3%.

[0095] The anion exchange membrane prepared in this embodiment was subjected to a small angle X-ray scattering test using Austrian Anton Paar SAXSess mc2. The test results are shown in FIG. Figure 6 As shown. Figure 6 The results show that the anion exchange membrane prepared in this embodiment has a long-range ordered microstructure. The main chain is simultaneously grafted with hydrophilic ion component side chains and hydrophobic side chains, which helps the anion exchange membrane to form hydrophilic and hydrophobic microphase separation, thereby promoting rapid ion conduction.

[0096] The alkali resistance stability test results of the anion exchange membrane prepared in this example are as follows: Figure 7 As shown. Figure 7 The results show that the anion exchange membrane prepared in this embodiment has an ionic conductivity of 131.2 mS / cm at 80°C before the above alkali resistance stability test, and after the test, the ionic conductivity at 80°C is 122.4 mS / cm, and the loss rate of ionic conductivity is 6.7%, which is less than 10%, proving that it has good alkali resistance stability.

[0097] Example 4 This embodiment provides an ionic polymer and an anion exchange membrane based on a flexible main chain, which are prepared by the following method: (1) In a 150 mL single-necked round-bottom flask, add 4.9 g of 1,7-dichloro-4-heptanone and 68 mL of trimethylamine methanol solution to 20 mL of methanol, and react under magnetic stirring at 40°C for 36 h under sealed conditions. After the reaction, remove the methanol solvent and excess unreacted trimethylamine on a rotary evaporator until a yellow oily viscous liquid is obtained, which is the product of quaternization of 1,7-dichloro-4-heptanone, N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-diammonium chloride.

[0098] (2) In a 100 mL two-necked round-bottom flask, 2 g of PVA was dissolved in 40 mL of DMSO at 80°C. After it was completely dissolved and cooled to room temperature, the above-synthesized N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-diammonium chloride, 6.8 g of 4'-(trifluoromethyl)acetophenone and 2.5 mL of trifluoromethanesulfonic acid were added. The temperature was raised to 80°C and the reaction was stirred for 24 h. After the reaction was completed, the reaction solution was added dropwise to a 0.5 M Na2CO3 aqueous solution to obtain an orange crude product. The crude product was crushed with a crusher, and the solution was washed with a large amount of deionized water until it was neutral. Finally, it was placed in a vacuum drying oven at 60°C and dried for 24 h to obtain a quaternized ketal polymer with a chloride anion and a hydrophobic side chain of 4'-(trifluoromethyl)phenylacetyl. Its specific structure is shown below:

[0099] (3) In a 50 mL two-necked round-bottom flask, add 0.4 g of the above-mentioned polymer electrolyte with chloride anion type and 4'-(trifluoromethyl)phenylacetyl as the hydrophobic side chain to 15 mL of DMSO solvent, stir at 60°C for 3 h until it is completely dissolved, cast the solution on a 8 cm × 8 cm flat and clean glass plate, and then place it in an 80°C electric oven to obtain a chloride anion exchange membrane with a thickness of about 45 μm through solvent evaporation. Finally, soak the chloride anion exchange membrane in a 1 mol / L potassium hydroxide solution at 60°C for 12 hours, replace the fresh alkali solution 3 times during the period, and finally rinse the residual floating alkali on the membrane surface with deionized water until the pH of the aqueous solution is 7, that is, the anion exchange membrane with hydroxide anion is obtained, and the anion exchange membrane is stored in deionized water with nitrogen. Its specific structure is shown below:

[0100] Among them, x is 0.1, y is 0.2, z is 0.4, and t is 0.

[0101] The IEC of the anion exchange membrane prepared in this example is 1.45 mmol·g -1 ; The ionic conductivity at 80℃ is 115.1mS·cm -1 The water content is 42.5%, the swelling rate is 7.9%; in the dry state, the tensile strength is 42.8 MPa, the elongation at break is 15.3%; the quality retention rate after the antioxidant stability test is 92.4%; the ionic conductivity retention rate after the alkali resistance stability test is 90.0%.

[0102] The water content test results of the anion exchange prepared in this example are as follows Figure 8 As shown. Figure 8 The results show that the water content of the anion exchange membrane prepared in this example at 80° C. is 42.5%.

[0103] The test results of the planar swelling rate of the anion exchange membrane prepared in this example are as follows: Fig. 9 As shown. Fig. 9 The results show that the anion exchange membrane prepared in this example has a planar swelling ratio of 7.9% at 80° C., and has high-humidity membrane planar dimensional stability.

[0104] Example 5 This embodiment provides an ionic polymer and an anion exchange membrane based on a flexible main chain, which are prepared by the following method: (1) In a 250 mL single-necked round-bottom flask, add 7.37 g of 1,7-dichloro-4-heptanone and 101.2 mL of trimethylamine methanol solution to 40 mL of methanol, and react under magnetic stirring at 40°C for 36 h under sealed conditions. After the reaction, remove the methanol solvent and excess unreacted trimethylamine on a rotary evaporator until a yellow oily viscous liquid is obtained, which is the product of quaternization of 1,7-dichloro-4-heptanone, N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-diammonium chloride.

[0105] (2) In a 100 mL two-necked round-bottom flask, 2 g of PVA was dissolved in 40 mL of DMSO at 80°C. After it was completely dissolved and cooled to room temperature, the above-synthesized N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-diammonium chloride, 8.7 g of 2,2,2,4'-tetrafluoroacetophenone and 1.5 mL of trifluoromethylbenzenesulfonic acid were added. The temperature was raised to 80°C and the reaction was stirred for 12 h. After the reaction was completed, the reaction solution was added dropwise to a 0.5 M Na2CO3 aqueous solution to obtain an orange crude product. The crude product was crushed with a crusher, and the solution was washed with a large amount of deionized water until it was neutral. Finally, it was placed in a vacuum drying oven at 60°C and dried for 24 h to obtain a quaternized ketal polymer with a chloride anion and a hydrophobic side chain of 2,2,2,4'-tetrafluoroacetophenone. Its specific structure is shown below:

[0106] (3) In a 50 mL two-necked round-bottom flask, add 0.4 g of the above-mentioned polymer electrolyte with chloride anion type and 2,2,2,4'-tetrafluoroacetophenone as the hydrophobic side chain to 15 mL of DMSO solvent, stir at 60°C for 4 h until it is completely dissolved, cast the solution on a 8 cm × 8 cm flat and clean glass plate, and then place it in an 80°C electric oven to obtain a chloride anion exchange membrane with a thickness of about 45 μm through solvent evaporation. Finally, soak the chloride anion exchange membrane in a 60°C, 1 mol / L potassium hydroxide solution for 12 hours, replace fresh alkali solution 3 times during the period, and finally rinse the residual floating alkali on the membrane surface with deionized water until the pH of the aqueous solution is 7, that is, the anion exchange membrane with hydroxide anion is obtained, and the anion exchange membrane is stored in deionized water with nitrogen. Its specific structure is shown below:

[0107] Among them, x is 0.15, y is 0.2, z is 0.3, and t is 0.

[0108] The IEC of the anion exchange membrane prepared in this example is 2.01 mmol·g -1; 80℃ ionic conductivity is 128.8mS·cm -1 The water content is 32.2%, the swelling rate is 5.6%; in the dry state, the tensile strength is 55.6 MPa, the elongation at break is 19.9%; the quality retention rate after the antioxidant stability test is 97.4%; the ionic conductivity retention rate after the alkali stability test is 96.8%.

[0109] The water electrolysis performance test results of the anion exchange membrane prepared in this embodiment in a zero-gap electrolyzer are shown in the attached figure. Fig.10 As shown. Fig.10 It can be seen that at 80°C the current density is 1.0 A cm -2 The corresponding voltage is 1.82 V and the current density is 1.0 A cm at 60 °C. -2 The corresponding voltage is 1.87 V.

[0110] Example 6 This embodiment provides an ionic polymer and an anion exchange membrane based on a flexible main chain, which are prepared by the following method: (1) In a 150 mL single-necked round-bottom flask, add 4.9 g of 1,7-dichloro-4-heptanone and 68 mL of trimethylamine methanol solution to 25 mL of methanol, and react under magnetic stirring at 40°C for 36 h under sealed conditions. After the reaction, remove the methanol solvent and excess unreacted trimethylamine on a rotary evaporator until a yellow oily viscous liquid is obtained, which is the product of quaternization of 1,7-dichloro-4-heptanone, N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-diammonium chloride.

[0111] (2) In a 100 mL two-necked round-bottom flask, 2 g of PVA was dissolved in 40 mL of DMSO at 80 °C. After it was completely dissolved and cooled to room temperature, the above-synthesized N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-diammonium chloride, 6.3 g of 2,2,2-trifluoroacetophenone and 1.8 mL of trifluoroacetic acid were added. The temperature was raised to 60 °C and the reaction was stirred for 24 h. After the reaction was completed, the reaction solution was added dropwise to a 0.5 M Na2CO3 aqueous solution to obtain an orange crude product. The crude product was crushed with a crusher, and the solution was washed with a large amount of deionized water until it was neutral. Finally, it was placed in a vacuum drying oven at 60 °C and dried for 24 h to obtain a quaternized ketal polymer with a chloride anion and a hydrophobic side chain of 2,2,2-trifluoroacetophenone. Its specific structure is shown below:

[0112] (3) In a 50 mL two-necked round-bottom flask, add 0.4 g of the above-mentioned polymer electrolyte with chloride anion type and 2,2,2-trifluoroacetophenone as the hydrophobic side chain to 15 mL of DMSO solvent, stir at 60°C for 3 h until it is completely dissolved, cast the solution on a 8 cm × 8 cm flat and clean glass plate, and then place it in an 80°C electric oven to obtain a chloride anion exchange membrane with a thickness of about 45 μm through solvent evaporation. Finally, soak the chloride anion exchange membrane in a 60°C, 1 mol / L potassium hydroxide solution for 12 hours, replace fresh alkali solution 3 times during the period, and finally rinse the residual floating alkali on the membrane surface with deionized water until the pH of the aqueous solution is 7, that is, the anion exchange membrane with hydroxide anion is obtained, and the anion exchange membrane is stored in deionized water with nitrogen. Its specific structure is shown below:

[0113] Among them, x is 0.1, y is 0.2, z is 0.4, and t is 0.

[0114] The IEC of the anion exchange membrane prepared in this example is 1.73 mmol·g -1 ; 80℃ ionic conductivity is 131.1mS·cm -1 The water content is 46.2%, the swelling rate is 8.8%; in the dry state, the tensile strength is 70.2 MPa, the elongation at break is 13.5%; after the alkali resistance stability test, the retention rate of ionic conductivity is 95.6%.

[0115] The results of the antioxidant stability test of the anion exchange membrane prepared in this example are as follows: Fig.11 As shown. Fig.11 The results show that the quality retention rate of the embodiment of the present invention is 98.1% after being immersed in Fenton's reagent at 40° C. for 168 hours.

[0116] Comparative example (Int J Hydrogen Energ. 46, 2021, 37007—37016) The comparative example uses polyvinyl alcohol as the polymer backbone, introduces brominated polyphenylene ether to increase the strength of the prepared anion exchange membrane, and uses 4-imidazole benzaldehyde as a crosslinking agent. On the one hand, 4-imidazole benzaldehyde reacts with the hydroxyl groups on the polyvinyl alcohol to form an aldol condensation reaction, and on the other hand, 4-imidazole benzaldehyde reacts with the brominated polyphenylene ether to form cations and realizes crosslinking of two different polymers. The best test example c-91 is selected as the comparative example of the present invention.

[0117] The optimized comparative example c-91 was o The fuel cell performance of C is 105 mW·cm -2 .

[0118] The optimized comparative example c-91 has a tensile strength of 47.0 MPa and an elongation at break of less than 10%.

[0119] The ionic conductivity of the optimized comparative example c-91 at 80 °C was 78.8 mS·cm -1 , the swelling rate is 14% and the water content is less than 55%.

[0120] The SAXS results of the optimized comparative example c-91 show that it has -1 There is an absorption peak.

[0121] The optimized comparative example c-91 was o After being immersed in Fenton's reagent of C for 168 h, the mass retention rate was 69.7%.

[0122] After the optimized comparative example c-91 was immersed in a 1 M NaOH solution at 80°C for 1000 h, the retention rate of ionic conductivity was 75%.

[0123] Table 1 shows the results of the anion exchange membranes prepared in the above Examples 1 to 6 and the results of the optimized comparative example c-91, which are summarized as follows: The test conditions for ion conductivity, swelling rate, water content, SAXS, mechanical properties, and antioxidant stability of the comparative example and the embodiment are the same. The test conditions for alkali resistance stability of the embodiment of the patent are 80°C and soaked in 1 mol / L KOH solution for 1440 hours. The test temperature for fuel cell performance test of the embodiment of the patent is 80 o C.

[0124] Table 1 Test results comparison table

[0125] It can be seen from the performance data in Table 1 above that: compared with the comparative example, the anion exchange membrane based on the flexible main chain prepared in Examples 1 to 6 of the present invention has the characteristics of excellent mechanical properties, high ionic conductivity, low swelling rate, high antioxidant stability, high alkali resistance stability, and high fuel cell performance.

[0126] An ion polymer and anion exchange membrane based on a flexible main chain prepared in Examples 1 to 6 of the present invention are composed of a hydroxyl-containing all-carbon flexible polymer main chain, a fluorinated side chain and an alkyl cation, and have a soluble ionomer. Since the main chain molecular weight of the embodiment is high, the prepared anion exchange membrane has more excellent mechanical properties. Since the SAXS scattering peak of the embodiment is higher, the distance d between the corresponding ion clusters is smaller, which is more conducive to the formation of continuous and broad ion channels by the ion clusters, promoting rapid ion conduction, and the embodiment has a higher ion exchange capacity, so the embodiment has a higher hydroxide ion conductivity. Since the embodiment does not contain unstable polymer main chains such as polyphenylene ether, the embodiment has more significant oxidation resistance and alkali resistance stability than the comparative example. Since the embodiment has an ion polymer corresponding to the anion exchange membrane as an ionomer when preparing the membrane electrode, and since the anion exchange membrane has a higher ionic conductivity, the embodiment shows better single cell discharge performance.

[0127] In summary, the anion exchange membrane based on the flexible main chain prepared by the present invention has high ionic conductivity, high chemical stability and high mechanical properties, and can be used as a diaphragm material for conducting ions in electrochemical devices, such as water electrolysis, fuel cells and other electrochemical devices. The ionic polymer based on the flexible main chain prepared by the present invention has good solubility, and the polymer solution can be used as an ionomer and a catalyst and a dispersant together to form a catalyst ink for preparing a membrane electrode, which can improve the operating performance of the device.

[0128] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An ionic polymer based on a flexible main chain, characterized in that: The polymer is represented by formula (I): (Ⅰ); In formula (I), x, y, z, and t all represent the molar proportion of each structural unit in the ionic polymer; wherein the value range of 2x+2y is 0.4~1.0, and 2x+2y+z+t=1.0; and R includes at least one benzene ring.

2. The ionic polymer based on a flexible main chain according to claim 1, characterized in that The value range of x is 0.1~0.5, the value range of y is 0.1~0.5, the value range of z is 0~0.6, and the value range of t is 0~0.

4.

3. A method for preparing an ionic polymer based on a flexible main chain as described in claim 1 or 2, wherein the ionic polymer based on a flexible main chain is prepared by acetalization and / or ketalization of a full-carbon flexible polymer main chain, an aldehyde or ketone and a quaternization product of 1,7-dichloro-4-heptanone.

4. The method for preparing an ionic polymer based on a flexible main chain according to claim 3, characterized in that: The all-carbon flexible polymer main chain is a hydroxyl-containing all-carbon flexible polymer main chain; the aldehyde or ketone is an aromatic aldehyde or aromatic ketone; The aromatic aldehyde is selected from at least one of p-fluorobenzaldehyde, 3,5-difluorobenzaldehyde, 3,4,5-trifluorobenzaldehyde, 2,3,4,5,6-pentafluorobenzaldehyde, 4-(trifluoromethyl)benzaldehyde, p-methylbenzaldehyde, benzaldehyde, m-methylbenzaldehyde or 3-(4-fluorophenyl)benzaldehyde, and / or the aromatic ketone is selected from at least one of 2,2,2,-trifluoroacetophenone, 4'-(trifluoromethyl)acetophenone or 2,2,2,4'-tetrafluoroacetophenone.

5. The method for preparing an ionic polymer based on a flexible main chain according to claim 4, characterized in that: The method comprises the following steps: S1. Mix 1,7-dichloro-4-heptanone and trimethylamine solution in a first organic solvent to obtain N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-diammonium chloride; S2, a hydroxyl-containing all-carbon flexible polymer main chain, the N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-diammonium chloride obtained in step S1 and aromatic aldehydes and / or aromatic ketones are mixed in the presence of a second organic solvent and a catalyst to obtain an ionic polymer based on a flexible main chain.

6. The method for preparing an ionic polymer based on a flexible main chain according to claim 5, characterized in that: In step S1, the amount of trimethylamine added is 3 to 5 times the molar amount of chlorine atoms in the 1,7-dichloro-4-heptanone; the mass volume ratio of the 1,7-dichloro-4-heptanone to the first organic solvent is 1 g: (5 to 10 mL); In step S2, the molar ratio of the N1,N1,N1,N7,N7,N7-hexamethyl-4-oxoheptane-1,7-diammonium chloride to the all-carbon flexible polymer main chain is (0.2~0.9):1; the molar ratio of the aromatic aldehyde and / or aromatic ketone to the all-carbon flexible polymer main chain is (0.2~0.8):1; the mass volume ratio of the all-carbon flexible polymer main chain to the second organic solvent is 1g:(20~40mL).

7. Use of the flexible main chain-based ionomer as claimed in claim 1 or 2 in anion exchange membranes and catalyst layer ionomers.

8. A method for preparing an anion exchange membrane, characterized in that: The anion exchange membrane is prepared from the ionic polymer based on a flexible main chain according to claim 1 or 2, or the anion exchange membrane is further prepared by the preparation method of the ionic polymer based on a flexible main chain according to any one of claims 3 to 6; the method comprises step S1 and step S2, and further comprises: S3, mixing the ionic polymer based on the flexible main chain of step S2 with a third organic solvent, drying the mixed solution to form a film, and immersing the film in an alkaline solution to obtain an anion exchange membrane whose anion is hydroxide; The mass volume ratio of the flexible main chain-based ionic polymer to the third organic solvent is 1 g: (20-50 mL).

9. An anion exchange membrane, characterized in that The anion exchange membrane is prepared by the method according to claim 8.

10. Use of the anion exchange membrane as claimed in claim 9 in fuel cells and water electrolysis.

Citation Information

Patent Citations

  • Highly acetalized, coarsely ground polyvinyl acetoacetals

    CN101454354A

  • Functionalized ketone-aldehyde condensation resins

    CN106046281A

  • Anion exchange membrane as well as preparation method and application thereof

    CN118659014A